Two dimensional efficiency measurements in vocational education: Evidence from Australia. Issue 2 (13th February 2017) - Fieger, Peter; Villano, Renato Andrin; Rice, John; Cooksey, Ray
Abstract : Purpose: In Australia, the vocational education and training (VET) sector accounts for approximately A8 billion of public spending, of which around A6.6 billion is spent on government providers that include Technical and Further Education (TAFE) institutes. The TAFE institutes in Australia are large, public VET providers, generally funded and managed by state government. Measuring the efficiency and effectiveness of TAFE institutes is of great interest to policy makers, regulators, consumers and to the institutions themselves. The paper aims to discuss these issues. Design/methodology/approach: In this study the authors use data relating to student cohort demographics, institutional characteristics and educational outcome data, while employing stochastic frontier analysis, to develop two distinct efficiency measures and models. The first model examines institutional efficiency in the transformation of financial resources into teaching loads. The second model evaluates efficiency in the transformation of institutional resources into post-study employment outcomes. K -means cluster analysis is used to establish groupings of similar institutes and subsequent canonical discriminant analysis is employed to develop a typology of these clusters. Findings: In both models the authors find significant inefficiencies in the Australian TAFE system. The relationship between both efficiency measures is then assessed. While there is no direct linear relationship, a distinct pattern could be detected. Finally the authors develop a typology of efficient institutions. Originality/value: This study contributes to the existing research by defining efficiency in vocational education in two distinct ways and by the utilisation of the derived efficiencies in the development of a typology of efficient institutes. In doing so, this research makes an original contribution to the understanding of the drivers of efficiency in vocational education.